2015
DOI: 10.1155/2015/207312
|View full text |Cite
|
Sign up to set email alerts
|

GABABReceptor Antagonist CGP46381 Inhibits Form-Deprivation Myopia Development in Guinea Pigs

Abstract: The aim was to investigate the effects of the GABAB receptor antagonist, CGP46381, on form-deprivation myopia (FDM) in guinea pigs. Twenty-four guinea pigs had monocular visual deprivation induced using a diffuser for 11 days (day 14 to 25). The deprived eyes were treated with daily subconjunctival injections (100 μl) of either 2% CGP46381, 0.2% CGP46381, or saline or received no injection. The fellow eyes were left untreated. Another six animals received no treatment. At the start and end of the treatment per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 40 publications
(56 reference statements)
2
9
0
Order By: Relevance
“…One hypothesis that emerges from these ideas is that the RGG is closely related to the occurrence and development of myopia. Previous study indicated that the contents of GABA and Glu were upregulated in myopia eyes in chick 53,54 and guinea pigs, 55 and our experimental results obtained the same result. Although in the normal development process the contents of Glu and GABA also were increased, the difference is that the RGG represented the balance between the excitatory and inhibitory neurotransmitters and always keeps an equilibrium state.…”
Section: Relationship Between the Rgg And Myopiasupporting
confidence: 88%
“…One hypothesis that emerges from these ideas is that the RGG is closely related to the occurrence and development of myopia. Previous study indicated that the contents of GABA and Glu were upregulated in myopia eyes in chick 53,54 and guinea pigs, 55 and our experimental results obtained the same result. Although in the normal development process the contents of Glu and GABA also were increased, the difference is that the RGG represented the balance between the excitatory and inhibitory neurotransmitters and always keeps an equilibrium state.…”
Section: Relationship Between the Rgg And Myopiasupporting
confidence: 88%
“…Specifically, the present findings are in agreement with previous reports of up-regulation of the NSF protein during lens-induced myopia in mouse [ 63 ], and up-regulation of the GABA A receptor mRNA and protein [ 107 ] and increased retinal GABA content during lens-induced myopia in guinea pigs [ 107 , 108 ]. This pattern of expression responses is also consistent with drug studies showing that GABA receptor antagonists inhibit myopia development [ 105 , 109 , 110 ]. Similarly, the GABA C receptor antagonist TPMPA enhanced the protective effect of short periods of normal vision on myopia development in chick, and the GABA A/C agonist Muscimol inhibited the protective effect of normal vision [ 111 ].…”
Section: Discussionsupporting
confidence: 87%
“…Experimental studies have revealed that several GABA receptor antagonists can retard the development of experimental myopia 697,698,705709. In FDM, antagonists against all three receptor subtypes can retard axial elongation to some extent in chicks and guinea pigs,698,709 while GABA A0r antagonists are effective at preventing the development of LIM in chicks 708.…”
Section: Biochemistry Of Emmetropization and Myopiamentioning
confidence: 99%